Diagnosis and prognosis of states in invitro fertilization based on the ontology knowledge - S. V. Denysenko (Zaporožskij Medicinskij Žurnal)
The present study focuses on the theoretical principles and conceptual possibilities of creating of the ontology knowledge of the in vitro fertilization. The multi-level ontology, each level of which is aimed to solve specific task, i.e. diagnosis, prediction, choice of treatment, is suggested. Compound of the subject ontology and task-oriented ontology enables significant reduction in the volume of information on each level.